Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.yexcr.2009.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ceacam1 in VEGF induced vasculogenesis of murine embryonic stem cell-derived embryoid bodies in 3D culture

Abstract: CEACAM1 (carcinoembryonic antigen-related cell adhesion molecule 1), a type I transmembrane glycoprotein involved in cell-cell adhesion has been shown to act as an angiogenic factor for mouse and human endothelial cells. Based on the ability of CEACAM1 to initiate lumen formation in human mammary epithelial cells grown in 3D culture (Matrigel), we hypothesized that murine CEACAM1 may play a similar role in vasculogenesis. In order to test this hypothesis, murine embryonic stem (ES) cells stimulated with VEGF w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 49 publications
(70 reference statements)
2
37
1
Order By: Relevance
“…Culture on Matrigel also induced KDR expression in MSCs which can further stimulate endothelial differentiation by increasing MSC sensitivity to VEGF present in culture medium. These results are similar to the ones obtained by Gu et al [75] while studying murine embryonic stem cells. They showed that increased ex-pression of endothelial markers is induced by extracellular matrix via CEACAM1, a glycoprotein involved in cell-cell adhesion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Culture on Matrigel also induced KDR expression in MSCs which can further stimulate endothelial differentiation by increasing MSC sensitivity to VEGF present in culture medium. These results are similar to the ones obtained by Gu et al [75] while studying murine embryonic stem cells. They showed that increased ex-pression of endothelial markers is induced by extracellular matrix via CEACAM1, a glycoprotein involved in cell-cell adhesion.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies demonstrate that vasculogenesis can also occur in adults, when endothelial progenitor and bone marrow-derived cells are recruited [74]. Alternatively, angiogenesis is the formation of new vessels by sprouting of existing capillaries and is dominant post-natally [75]. Being able to control and direct both processes opens the possibility to create capillary networks both within tissues as well as in in vitro engineered constructs.…”
Section: Vasculogenesis and Angiogenesismentioning
confidence: 99%
“…This protein is widely expressed in a variety of proliferating and quiescent epithelial, endothelial, and haematopoietic cells [2]. CEACAM1 is involved in a variety of cell biological events, such as morphogenesis [3], vasculogenesis [4], cell motility [5], cell proliferation [6,7], infection, and inflammation [2]. CEACAM1 exists in 11 known isoforms, resulting from differential splicing and proteolytic processing.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that DBHA inhibited neovascularization by suppressing microvessel sprouting in mES cell-derived EBs. The anti-angiogenic activity of DBHA was confirmed by an in vitro angiogenesis sprouting model system using the mES/EB model [44]. Previously, we have found that mES cell-derived EBs matured in a type-I collagen gel and formed capillary-like structures, as observed by morphological changes (3-D culture) and the expression of PECAM (2-D culture).…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, the mES/EB-derived 3D model is recognized as an excellent system to examine anti-angiogenic activity [41,42,43,44]. Recently, we demonstrated the anti-angiogenic activity of honokiol, a natural angiogenesis inhibitor, with the mES cell-derived EB system [13].…”
Section: Resultsmentioning
confidence: 99%